Influence of gut microbiota dysbiosis on brain function: a systematic review - Almeida, Cátia (2022)
Background: For almost a century it has been recognized that human possess a varied and dens microbial ecosystem called the human microbiota, yet we are still beginning to understand many of the roles that these microorganisms play in human health and development. It is thought that under certain circumstances such as dysbiosis, the microbiota can cause diseases, where the central nervous system (CNS) has an important relevance and where the “gut-brain axis” will play a major role. Aims: This review investigated the influence of the gut microbiota on brain function, trying to demonstrate whether dysbiosis influences CNS diseases or whether it is the disease that causes dysbiosis, highlighting the existing literature within this field. Methods:We performed a systematic literature search in EMBASE, PubMed, and Cochrane combining the terms “gut microbiota,” “dysbiosis,” and “CNS diseases” to identify those whom reported some influence or relation between dysbiosis of gut microbiota and CNS diseases. For the present systematic review, we only included systematic reviews or meta-analysis. Results: The EMBASE, PubMed, and Cochrane were systematically searched, considering only systematic reviews or metaanalysis. Nine studies comprising 705 articles were included in this review. Those 9 systematic reviews consist in 2 about autism spectrum disorder, 1 in dementia, 1 in depression, 2 in autoimmune diseases, 1 in schizophrenia, and 2 in some altered brain function. Available data characterizing several neural diseases demonstrate a significant correlation between dysbiosis and CNS diseases, strengthen the evidence that dysbiosis of gut microbiota may correlate with abnormalities in CNS patients. Conclusions: Although there is a clear need for more investigations to better understand the role of the gut microbiota in CNS diseases, the modulation of the nervous system by the microbiota is clear, continuing to be the subject of continuous research. We need to fully understand the mechanisms by which the microbiota interacts with the human brain, and therefore what’s the connection between dysbiosis and pathologies such depression, dementia, autism, or schizophrenia.